Disabilities as a Gift and Grace in Family Life: Transforming The Parent–Child Relationship Through John Paul II's Theology of The Body - Fabianus Selatang; FX Eko Armada Riyanto; Raymundus I Made Sudhiarsa (CV. AFDIFAL MAJU BERKAH, 2026)
Families raising children with disabilities often experience profound relational, emotional, and existential challenges that reshape everyday life. Within these complex dynamics, the parent–child relationship becomes a privileged locus for encountering vulnerability, gift, and mutual transformation. This study aims to explore how the embodied experiences of parents and children with disabilities can be understood and renewed through John Paul II's Theology of the Body, particularly his insights on embodiment, gift, and relationality. Employing a qualitative phenomenological approach, this research gathers and analyses in-depth interviews with parents of children with disabilities to uncover the lived meanings embedded in their daily interactions. The analysis is guided by the theological framework of the Theology of the Body, complemented by Emmanuel Levinas's ethics of the Other and relational perspectives within contemporary pastoral theology. The findings reveal that parents experience their child's body not as a limitation but as an embodied gift that calls forth deeper empathy, self-giving love, and a renewed sense of human dignity. The child's vulnerability becomes a place of grace that transforms parental identity, spirituality, and the understanding of relational reciprocity. Moreover, the study highlights how embodied encounters foster resilience, reshape family practices, and open new horizons for pastoral accompaniment. In conclusion, the integration of phenomenological insights and theological anthropology demonstrates that disability, when viewed through the lens of the Theology of the Body, becomes a transformative pathway of grace that reconfigures the parent–child relationship and enriches the wider pastoral and theological discourse on embodiment.